Une stratégie analytique et opérationnelle pour les transformations du territoire métropolitain de Vérone : paysage-infrastructure - Daniela Perrotti; Chiara Locardi (Projets de Paysage)
The research on the Verona urban landscape transformations generated from the new pan-European infrastructure network presents the opportunity to verify the close and reciprocal relationship between two different entities : Infrastructure and Landscape. The analytic approach Landscape-Infrastructure works towards the strategic and functional integration of the new infrastructures in the metropolitan landscape of Verona and it brings out the potential of the production landscape in the territorial network. Landscape-Infrastructure is a connection device composed of three components (urban tissue, infrastructure network and free ground) that are contemporarily analysed and compared in order to strengthen and hierarchise the metropolitan landscape through its urban and geographical structure. In this approach the edge express the physical space of the morphological, geographic and connective potentials for each development area and it also represents the territory of exchange between bordering micro-regions in the urban ecosystem.